Conservative Treatment of a Gossypiboma Causing Uterine Wound Dehiscence. (11th September 2013) - Usta, Taner A.; Yildirim, Dogukan; Ozyurek, Sefik E.; Gundogdu, Elif C.
Abstract : We present a rare case with gossypiboma following cesarean section which led to uterine wound dehiscence. A 30-year-old woman had been submitted to an emergency cesarean section 4 months previously at another hospital. Clinical and ultrasound findings revealed a large intra-abdominal mass and diffuse peritonitis. At laparotomy, a gossypiboma causing an abscess and uterine wound dehiscence with necrosis of the margins was detected. We performed repetitive wound debridements under broad-spectrum antibiotic cover and eventually resutured the incision. Although hysterectomy has so far been the choice of treatment in the literature once a uterine wound dehiscence had occurred, it was possible in this case to preserve the uterus.